Identifikasi dan Kekerabatan Fenotipe Ikan Familia Cyprinidae Asal Waduk Sempor, Jawa Tengah - Pradina Damayanti; Dian Bhagawati; Nuning Setyaningrum (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2022)
The basic data needed to support reservoir management includes information on fish diversity. Research has been conducted to determine the diversity, phenetic relationship, and simple identification keys for Cyprinidae fish from Sempor Reservoir, Sempor District, Kebumen Regency, Central Java Province. The study was carried out in the period August 2020 to February 2021 with a survey method, and sampling using a purposive random sampling technique. The variables observed were phenotypic characters and species kinship relationships. Parameters observed were morphological performance. Fish body measurements were carried out using standard morphometry. Calculations were made on the number of species and the meristics of each species. The data obtained were analyzed using the NTSYS 2.02i application. to get kinship. Morphological performance was analyzed descriptively. During the research, five fish species from the Familia Cyprinidae were found, including Barbodes binotatus, Barbonymus balleroides, Osteochilus vittatus, Puntius sp., and Rasbora argyrotaenia. The closest phenetic relationship is between B. binotatus and Puntius sp. with a similarity index value of 0.909. The furthest relationship between R. argyrotaenia and B. binotatus with a similarity index value of 0.742. Morphological performance that can be used as a key identification character in Cyprinidae fish from Sempor Reservoir is the presence of a black spot on the tail rod; the reddish color of the abdominal fins, anal fins, and eyes; and a silvery color shaped like a ribbon along the body.